Nature-Based Tourism: Motivation and Subjective Well-Being - Kim, H.; Lee, S.; Uysal, Muzaffer; Kim, J.; Ahn, K. (Routledge, 2015)
Â© 2015 Taylor & Francis. The purpose of this study is to understand hiking-tourist behavior by exploring tourist motivation, personal values, subjective well-being, and revisit intention. The study demonstrates the theoretical and empirical evidence of the relationships among the four constructs. Using a sample drawn from tourists in South Korea, an exploratory factor analysis (EFA) is carried out. As a result, “enjoying the natural environment and escaping from daily life”, “pursuing new type of travel”, “pursuing healthy life”, and “pursuing intimacy” are classified as motivations for hiking tourists. Moreover, in order to investigate the relevant relationships among the four constructs, a structural equation modeling (SEM) approach is used. The results indicate that revisit intention is affected by tourist motivation and subjective well-being. Furthermore, hiking-tourists’ motivation and personal values are effective predictors of subjective well-being.